2019
DOI: 10.1002/vnl.21724
|View full text |Cite
|
Sign up to set email alerts
|

Silane Modification of Carbon Nanotubes and Preparation of Silane Cross‐Linked LLDPE/MWCNT Nanocomposites

Abstract: The objective of this study is to investigate the effects of carbon nanotube (CNT) content, surface modification, and silane cross-linking on mechanical and electrical properties of linear low-density polyethylene/multiwall CNT nanocomposites. CNTs were functionalized by vinyltriethoxysilane to incorporate the ─O─C2H5 functional groups and were melt-blended with polyethylene. Silane-grafted polyethylene was then moisture crosslinked. Silanization of CNT was confirmed by Fourier transform infrared spectroscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Since AgNWs [182,183] are highly electrically conductive at low concentrations, electrodes with great transparency could be achieved using AgNWs. This can be considered a significant advantage of using AgNWs since conventional conductive materials used for flexible devices such as carbon nanotubes [184] exhibit relatively poor transparency. Experimental results also demonstrated the long-term stability of AgNW-based flexible microfluidic circuits over various deformations.…”
Section: Flexible Circuits and Interconnectsmentioning
confidence: 99%
“…Since AgNWs [182,183] are highly electrically conductive at low concentrations, electrodes with great transparency could be achieved using AgNWs. This can be considered a significant advantage of using AgNWs since conventional conductive materials used for flexible devices such as carbon nanotubes [184] exhibit relatively poor transparency. Experimental results also demonstrated the long-term stability of AgNW-based flexible microfluidic circuits over various deformations.…”
Section: Flexible Circuits and Interconnectsmentioning
confidence: 99%
“…Dependence of (a) complex viscosity, (b) storage modulus ( G′ ) and loss modulus ( G″ ) plotted against the angular frequency at 160°C. (c) Comparison in viscosity between the LLDPE/L130 in this study and reported representative inorganic particulate‐filled LLDPE composites 32–41 . [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 91%
“…Polyethylene (PE), as a thermoplastic material, is widely used in different fields of life and industry due to its superior low-temperature resistance, chemical stability, and toughness. [1][2][3] However, the flammability of PE has limited its wider application. Therefore, many flame retardants have been used to improve the flame retardance of PE.…”
Section: Introductionmentioning
confidence: 99%